The Pathogenesis, Diagnosis, Treatment, and Etiology of Acute and Chronic Gastritis - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Bioscience and Clinical Integrity, 2025)
These days, inflammation of the stomach mucosa is one of the symptoms of the disease known as gastritis. The author of this essay focuses particularly on the fact that inflammation in gastritis is frequently caused by infection with the same bacterium that causes the majority of stomach ulcers. The causes of this illness are examined in detail in this text, with the most prevalent being excessive use of painkillers, alcohol, and an unbalanced diet. A more thorough examination of the diseased process's clinical expression holds the promise for future research.